Implementation of the Blended Learning Model through Interactive Learning Multimedia to Improve Understanding of the Concept of Harmony in the Ecosystem of Science Subjects for Grade V Elementary School Students - Khiyaratun Nadhifah; I Wayan Widana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The implementation of this learning aims to be able to implement the Blended Learning learning model through interactive learning multimedia in improving the understanding of the concept of Harmony in Ecosystem material for fifth grade students of UPTD SD Negeri Bluru. The purpose of blended learning is to increase flexibility, optimize time and increase interaction. To obtain accurate results, the implementation procedure is carried out using an experimental method with a pretest-posttest design with a control group. The implementation of learning is carried out by integrating two types of online and face-to-face learning based on interactive learning multimedia which is expected to create a more meaningful learning experience and improve students' understanding of ecosystem concepts. The results of the study showed a significant increase in students' understanding of concepts after participating in blended-learning learning. In addition, students also showed a higher interest in learning and were more active in participating in learning activities. Blended learning will continue to be improved and updated so that it can be used in other subjects with relevant material. In this case, there needs to be reflection, evaluation and follow-up systematically and comprehensively.